Strengthening Law Enforcement Against Illegal Coal Mining Based on Sustainable Development Goals to Achieve Sustainable Mining Governance in Indonesia - Sunardi Sunardi; Tricho Dike Fierrera; Zainal Arifin Hoesein (International Journal of Sociology and Law, 2026)
Coal mining is a strategic sector that plays an important role in promoting national economic growth and increasing state revenue. However, illegal coal mining practices remain a serious problem as they cause environmental damage, state economic losses, social conflicts, and hinder the realization of sustainable mining governance. Existing law enforcement efforts have not fully provided a deterrent effect due to weak supervision, limited inter-agency coordination, and the suboptimal implementation of legal provisions in the mining sector. This condition indicates the need to strengthen law enforcement approaches that are not only oriented toward imposing sanctions but are also aligned with the principles of sustainable development as reflected in the Sustainable Development Goals (SDGs). This study aims to analyze the regulation and implementation of law enforcement against illegal coal mining in Indonesia, identify factors affecting the effectiveness of law enforcement, and formulate a concept for strengthening SDG-based law enforcement to achieve sustainable mining governance. This research employs a normative juridical method using statutory, conceptual, and case approaches. Legal materials were obtained through a literature study of relevant laws and regulations, court decisions, and scientific literature, which were then analyzed qualitatively. The results of the study indicate that strengthening law enforcement needs to be carried out through regulatory harmonization, optimization of supervision, improvement of inter-agency coordination, implementation of proportional and consistent sanctions, and integration of SDG principles into mining policies. These efforts are expected to establish fair coal mining governance, provide legal certainty, protect the environment, and support sustainable national development.